2017
DOI: 10.1016/j.athoracsur.2016.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Years of Life Lost After Complications of Coronary Artery Bypass Operations

Abstract: Acute cardiac arrest, reoperation for other cardiac reasons, new dialysis, atrial fibrillation, and prolonged mechanical ventilation are associated with the largest increase in attributable deaths. Prevention and treatment of these complications may improve mortality rates after cardiac operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…1,3,5,6,8,9,11 We found that mechanical ventilation on days 7, 14, 21, and 28 was strongly associated Intensive Care Unit with operative mortality, similar to noncardiac surgery patients and cardiac surgery patients. 6,23,24 While we found several processes of care, such as catecholamine use and transfusions to be associated with mortality, which is similar to other studies, notably, we did not find an association between renal replacement therapy and mortality. 1,25 While there is an association between renal replacement therapy and mortality in ICU patients, its status in cardiac surgery patients with prolonged ICU stays is less clear.…”
Section: Discussionsupporting
confidence: 89%
“…1,3,5,6,8,9,11 We found that mechanical ventilation on days 7, 14, 21, and 28 was strongly associated Intensive Care Unit with operative mortality, similar to noncardiac surgery patients and cardiac surgery patients. 6,23,24 While we found several processes of care, such as catecholamine use and transfusions to be associated with mortality, which is similar to other studies, notably, we did not find an association between renal replacement therapy and mortality. 1,25 While there is an association between renal replacement therapy and mortality in ICU patients, its status in cardiac surgery patients with prolonged ICU stays is less clear.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the steady improvements in survival and operative safety, postoperative complications still cause significant morbidity and suffer among operated patients [ 5 , 14 ]. The impact of postoperative complications is mainly evaluated in survival [ 14 , 15 ] and economical [ 16 ] perspectives. However, the effect of postoperative complications on patients’ quality of life in long term is hitherto unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of postoperative complications after CABG surgery ranges between 30 and 40% depending on the number of different complication included in the studies [ 14 , 15 , 20 ]. These findings are in line with the incidence of postoperative complication, 40%, represented in our study cohort.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Following failed extubation, these patients are more likely to experience prolonged intensive care unit stay, hospitalisation, excess morbidity and subsequent mortality. 2–6 …”
Section: Introductionmentioning
confidence: 99%
“…1 Following failed extubation, these patients are more likely to experience prolonged intensive care unit stay, hospitalisation, excess morbidity and subsequent mortality. [2][3][4][5][6] Treatment with heated, humidified, highflow nasal cannula (HFNC) oxygen has been proposed a therapy for hypoxic respiratory failure in numerous clinical settings. 7 HFNC can deliver up to 100% oxygen at a maximum flow of 60 L/min via nasal cannula, offering important physiological advantages, including improved dead space ventilation, mucociliary clearance and offering some positive end expiratory pressure, compared with standard oxygen therapy.…”
Section: Introductionmentioning
confidence: 99%